Isorhamnetin augments the anti-tumor effect of capeciatbine through the negative regulation of NF-?B signaling cascade in gastric cancer - Manu, K.; Shanmugam, M.; Ramachandran, L.; Li, F.; Siveen, K.; Chinnathambi, A.; Zayed, M.; Alharbi, S.; Arfuso, Frank; Kumar, A.; Ahn, K.; Sethi, G. (Elsevier Ireland Ltd, 2015)
Development of drug resistance to standard chemotherapy is a common phenomenon that leads to poor prognosis in patients. Thus, novel agents that can attenuate chemoresistance are urgently needed. Therefore, we analyzed whether isorhamnetin (IH), a 3'-O-methylated metabolite of quercetin, can enhance the potential efficacy of capecitabine in gastric cancer. The potential effect of IH on viability was analyzed by MTT assay, apoptosis by flow cytometric analysis, and NF-?B activation by DNA binding as well as Western blot assays. The in vivo effect of IH was also examined on the growth of subcutaneously implanted tumors in nude mice. IH inhibited the viability, potentiated the apoptotic effects of capecitabine, abrogated NF-?B activation, and suppressed the expression of various NF-?B regulated gene products in tumor cells. In a gastric cancer xenograft model, administration of IH alone (1 mg/kg body weight, i.p.) significantly suppressed the tumor growth alone as well as in combination with capecitabine. IH further reduced NF-?B activation and the expression of various proliferative and oncogenic biomarkers in tumor tissues. Overall, our results demonstrate that IH can significantly enhance the anti-tumor effects of capecitabine through the negative regulation of NF-?B regulated oncogenic genes.